2004
DOI: 10.1063/1.1774249
|View full text |Cite
|
Sign up to set email alerts
|

Fullerenes surface gratings for liquid crystal alignment

Abstract: We report on the formation of surface structures by photopolymerization of C60 and C70 in isotropic solutions. The structures show the same periodicity of the interference patterns used for photopolymerization and behave as diffraction gratings. Mass spectrometry confirmed that the deposited material contains polymerized fullerenes, while the structure of the deposit was investigated by atomic force microscopy. We have also shown that these periodic structures are useful for inducing mesophase orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Dispersions of gold spheres, nickel bowls, and carbon nanotubes are good examples of agents achieving the uniform LC alignments by optimizing their shape, size, and concentration, resulting in this exciting invention being geared toward the one‐bottle approach . In addition, the use of nanoparticles in LC media has improved the electro‐optical performances, achieving high contrast ratios, fast response times, and low driving voltages . Therefore, many organic chemists and device physicists have focused on the nanoparticle‐induced automatic LC alignment for the technologically significant nanoscale manufacturing .…”
Section: Introductionmentioning
confidence: 99%
“…Dispersions of gold spheres, nickel bowls, and carbon nanotubes are good examples of agents achieving the uniform LC alignments by optimizing their shape, size, and concentration, resulting in this exciting invention being geared toward the one‐bottle approach . In addition, the use of nanoparticles in LC media has improved the electro‐optical performances, achieving high contrast ratios, fast response times, and low driving voltages . Therefore, many organic chemists and device physicists have focused on the nanoparticle‐induced automatic LC alignment for the technologically significant nanoscale manufacturing .…”
Section: Introductionmentioning
confidence: 99%
“…fullerenes, bridging the 'gap' between metallic and semiconducting nanoparticles and CNTs have also been used to manipulate the properties of LCs. For example, Golemme et al demonstrated the use of diffraction gratings made of photopolymerized C 60 and C 70 that can serve as planar alignment layers for N-LCs, 46 and enhanced switching speed in fullerene-doped nematic phases. 47 As for non-nematic LCD technologies such as surface-stabilized ferroelectric LC (SSFLC) displays, examples dealing with nanoparticle-filled smectic phases in general are rather rare.…”
Section: Hao Qimentioning
confidence: 99%
“…The Au-NP properties can be tuned with LCs which initiated changes in the localized surface plasmon resonances [28]. The liquid crystals are unique candidates to manipulate Au-NP assembly [29][30][31], as well as their electronic and optical properties for novel nanoscale devices [32]. In addition, the liquid crystals properties can also be affected by the Au-NP, such as electro-optic properties [33] and alignment of LC molecules used in the display applications [23].…”
Section: Introductionmentioning
confidence: 99%